2020
DOI: 10.1051/0004-6361/202038696
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties of turbulent fluctuations associated with electron-only magnetic reconnection

Abstract: Context. Recent satellite measurements in the turbulent magnetosheath of Earth have given evidence of an unusual reconnection mechanism that is driven exclusively by electrons. This newly observed process was called electron-only reconnection, and its interplay with plasma turbulence is a matter of great debate. Aims. By using 2D-3V hybrid Vlasov–Maxwell simulations of freely decaying plasma turbulence, we study the role of electron-only reconnection in the development of plasma turbulence. In particular, we s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Idealized PIC simulations of laminar magnetic reconnection, in which the length of the reconnecting current sheets were artificially varied by changing the size of the simulation domain, have shown that if the length of the current sheet along the outflow direction is less than ∼ 40d i then the ions will only partially couple to the reconnected magnetic field, resulting in reduced ion jet speeds relative to expectations, and if the the current sheet length is less than ∼ 10d i , the ion jets are virtually non-existent and are consistent with electrononly reconnection 78 . More recent PIC and Vlasov simulations of plasma turbulence have also begun to confirm that turbulent dynamics can generate electron-only reconnection [81][82][83] .…”
Section: Introductionmentioning
confidence: 98%
“…Idealized PIC simulations of laminar magnetic reconnection, in which the length of the reconnecting current sheets were artificially varied by changing the size of the simulation domain, have shown that if the length of the current sheet along the outflow direction is less than ∼ 40d i then the ions will only partially couple to the reconnected magnetic field, resulting in reduced ion jet speeds relative to expectations, and if the the current sheet length is less than ∼ 10d i , the ion jets are virtually non-existent and are consistent with electrononly reconnection 78 . More recent PIC and Vlasov simulations of plasma turbulence have also begun to confirm that turbulent dynamics can generate electron-only reconnection [81][82][83] .…”
Section: Introductionmentioning
confidence: 98%
“…It is known that plasma turbulence naturally tends to generate magnetic field shears associated with intense current sheets (Servidio et al 2009(Servidio et al , 2010. The role of these structures in turbulence has been extensively studied in relation to the occurrence of energetic phenomena, such as reconnection, that can influence the properties of the turbulent cascade and of dissipation Franci et al 2017;Dong et al 2018;Comisso et al 2018;Arrò et al 2020). Here we have shown that electron velocity shears are also spontaneously generated by the turbulence and their disruption via the EKHI supports the cascade of energy from large to sub-ion scales, producing kinetic scale EVMHs that possibly contribute to dissipation.…”
Section: Discussionmentioning
confidence: 99%
“…An immediate application of this novel theory is to estimate energy dissipation in localized structures (e.g., reconnecting current sheets) frequently reported in numerical simulations [55] and spacecraft observations in the near-Earth space [28,56]. Indeed, even if the theory is based on a fluid (HMHD) model, the fact that π (x) is shown to reflect local dissipation (within the aforementioned assumptions) regardless of the explicit form of the dissipation operators makes it particularly relevant to collisionless plasmas where the damping of the fluid and electromagnetic fluctuations is believed to originate from kinetic processes that would show up in the moment equation as complex damping operators d ν , d η .…”
Section: Discussionmentioning
confidence: 99%